Rational Engineering of Anode Current Collector for Dendrite-Free Lithium Deposition: Strategy, Application, and Perspective - Li, Nanrui; Jia, Tianqi; Liu, Yanru; Huang, Shifei; Kang, Feiyu; Cao, Yidan (Frontiers in Chemistry, 2022)
Lithium metal anode have attracted extensive attention due to its high theoretical capacity and low redox potential. However, the low coulombic efficiency, serious parasitic reaction, large volume change and dendrite growth during cycling have hindered the practical application. The engineering of anode current collector provides important advances to solve these problems, eliminate excess lithium usage, and substantially increase the energy density. In this review, we summarize the engineering strategies of anode current collector with emphasis on different methods and applications in lithium metal-based systems. Finally, the perspectives and challenges of current collector engineering for lithium metal anode are discussed.